Mini-Review on Lipofuscin and Aging: Focusing on The Molecular Interface, The Biological Recycling Mechanism, Oxidative Stress, and The Gut-Brain Axis Functionality - Ovidiu-Dumitru Ilie; Alin Ciobica; Sorin Riga; Nitasha Dhunna; Jack McKenna; Ioannis Mavroudis; Bogdan Doroftei; Adela-Magdalena Ciobanu; Dan Riga (Medicina, 2020)
Intra-lysosomal accumulation of the autofluorescent “residue” known as lipofuscin, which is found within postmitotic cells, remains controversial. Although it was considered a harmless hallmark of aging, its presence is detrimental as it continually accumulates. The latest evidence highlighted that lipofuscin strongly correlates with the excessive production of reactive oxygen species; however, despite this, lipofuscin cannot be removed by the biological recycling mechanisms. The antagonistic effects exerted at the DNA level culminate in a dysregulation of the cell cycle, by inducing a loss of the entire internal environment and abnormal gene(s) expression. Additionally, it appears that a crucial role in the production of reactive oxygen species can be attributed to gut microbiota, due to their ability to shape our behavior and neurodevelopment through their maintenance of the central nervous system.